FUNGSI PENDAPATAN USAHA BUDIDAYA IKAN MAS KERAMBA DI DESA SIMPANG TIGA KECAMATAN LAMPIHONG KABUPATEN BALANGAN PROPINSI KALIMANTAN SELATAN - Miranda Romauly (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The purpose of this study was to identify factors that significantly on affecting  revenue carp farming cages in the village of Simpang Tiga, Lampihong’s’s district Balangan’s. Regency.   The function of Revenue include independent variables of charge cages, seed costs, feed costs and  labor costs.  The results gained Adjusted R2 value is equal to 0.744. Means that 74.4% of Revenue variation can be explained by the variable cost of cages, the cost of seed, feed costs, and labor costs. While 25.6% is influenced by other  variables not included in the regression model. The value of F test is 32.673 with significant value 0.000 shows all the variables in the model simultaneously affect revenue variation of carp farming cages. While the t test results showed the dominant variable affecting the revenue is variable seed costs, feed costs, and the cost of cages, while labor costs have no effect on revemue carp fish cages. Regression coefficient -0.078 cages variable costs, variable regression coefficient seed costs amounted to 0.476 and the regression coefficients for the variables feed 0,580. So in an effort to increase revenue should improving seed and feed while the cages do not need to be added as a negative amount.